A Carbene‐Rich but Carbonyl‐Poor [Ir6(IMe)8(CO)2H14]2+ Polyhydride Cluster as a Deactivation Product from Catalytic Glycerol Dehydrogenation1. (22nd September 2014) - Campos, Jesús; Sharninghausen, Liam S.; Crabtree, Robert H.; Balcells, David
Abstract The title cluster, a deactivation product in the catalytic dehydrogenation of glycerol, was characterized by XRD, DFT calculations, HRMS, FTIR spectroscopy, and NMR spectroscopy. Experimental/computational studies located the 14 H ligands, and all 1H and 13C{1H} NMR resonances were assigned. The structure contains an unprecedented Ir6H14 core with two CO and eight IMe ligands.